NUTRITIONAL EVALUATION AND CONSUMER ACCEPTABILITY OF BISCUITS MADE FROM BLENDS OF ORANGE SWEET POTATO (OSP) PUREE AND WHEAT FLOUR - SAMUEL , F. O.; AKOMOLAFE, A.A.; EYINLA, T. E. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2021)
The potential of biofortified Orange Sweet Potato (OSP) has been successfully evaluated in the search of interventions to reduce the burden of Vitamin A deficiencies.  Production of biscuits with inclusion of OSP, particularly its puree, to improve pro-vitamin A intake (through its high β-carotene) has not been fully explored. This study therefore evaluated nutrient and anti-nutrient composition of biscuits produced from different ratio blends of OSP puree-Wheat flour and also tested their acceptability. Varying proportions of OSP puree-Wheat flour: 10:90 (A2), 20:80 (A3), 30:70 (A4), 40:60 (A5), were evaluated. Proximate, β-carotene, mineral, phytate, and tannin content were determined. The moisture, protein, fat, ash and carbohydrate content of the biscuits ranged thus: 9.41– 15.27%, 11.56–13.10%, 5.19–6.69%, 0.61–0.97% and 62.20–68.43% respectively. Substitution increased β-carotene from 1.81 µg/g in 100% wheat to 8.78 µg/g in sample A5. Additionally, substitution lowered anti-nutrient content (phytate and tannins) from 10.30mg and 11.94GAE in 100% wheat to 4.10mg and 6.30GAE in the biscuits. These increases and decreases were found to be statistically significantly (p<0.05). Sensory attributes of the OSP blends showed that the 30:70 and 10:90 proportions had highest and lowest overall acceptability respectively. Overall, this study shows that addition of OSP puree to wheat flour to produce biscuits improved the β-carotene contents of the resulting products. Willingness to buy/feed children also indicate a favourable stance towards the new products.  These biscuits can be used as food vehicles in addressing deficiencies of Vitamin A which are still common among children in Sub-Saharan Africa.